Răspuns :
( √2√2 -3)² = I 2√2 -3 I = numar negativ = 3 - 2√2
in radical formam binom 9 = 8 +1
4√2 = 2· 2√2 ·1 daca a = 2√2 ; a² = ( 2√2 )²=4·2 =8
b=1 b²=1
-----------------------------------------
a² + b² = 8 +1 =9
9 + 4√2 = 8 + 4√2 + 1 = ( 2√2 )² + 4√2 +1 = ( 2√2 + 1 )²
3 -2√2 + 2√2 + 1 4
ex. =------------------------ = -------
x -1 x -1
in radical formam binom 9 = 8 +1
4√2 = 2· 2√2 ·1 daca a = 2√2 ; a² = ( 2√2 )²=4·2 =8
b=1 b²=1
-----------------------------------------
a² + b² = 8 +1 =9
9 + 4√2 = 8 + 4√2 + 1 = ( 2√2 )² + 4√2 +1 = ( 2√2 + 1 )²
3 -2√2 + 2√2 + 1 4
ex. =------------------------ = -------
x -1 x -1